2012
DOI: 10.1002/ar.22497
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Anti‐Tumor Activity in Bladder Cancer T24 Cell Line Through Induction of Cell‐Cycle Arrest and Apoptosis

Abstract: Bladder cancer is the most common neoplasm in the urinary system. This study assesses arctigenin anti-tumor activity in human bladder cancer T24 cells in vitro and the underlying molecular events. The flow cytometry analysis was used to detect cell-cycle distribution and apoptosis. Western blotting was used to detect changes in protein expression. The data showed that arctigenin treatment reduced viability of bladder cancer T24 cells in a dose-and time-dependent manner after treatment with arctigenin (10, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Paeoniflorin is one of the active ingredients present in Paeonia, and is able to suppress proliferation and trigger apoptosis in human glioma cells via the upregulation of microRNA-16 and the downregulation of MMP-9 expression (13). Previous studies have demonstrated that arctigenin exhibits antitumor effects in various types of tumor cells (7)(8)(9)14). In the present study, it was identified that arctigenin, within the concentration range evaluated, significantly suppressed the viability of the U87MG and T98G cells, as compared with the vehicle-treated cells, in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin is one of the active ingredients present in Paeonia, and is able to suppress proliferation and trigger apoptosis in human glioma cells via the upregulation of microRNA-16 and the downregulation of MMP-9 expression (13). Previous studies have demonstrated that arctigenin exhibits antitumor effects in various types of tumor cells (7)(8)(9)14). In the present study, it was identified that arctigenin, within the concentration range evaluated, significantly suppressed the viability of the U87MG and T98G cells, as compared with the vehicle-treated cells, in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin (ATG) is a pharmaceutically active substance isolated from the seeds of Arctium lappa L. (commonly called greater burdock), and several investigators have shown it has anti-viral, Arctigenin (ATG) is a pharmaceutically active substance isolated from the seeds of Arctium lappa L. (commonly called greater burdock), and several investigators have shown it has anti-viral, antiinflammatory, anti-cancer, and immunomodulatory activities [9][10][11][12][13]. The anti-cancer activity of ATG has been reported to due to the induction of apoptosis mediated by mitochondrial disruption and cell cycle arrest in breast, lung, bladder, gastric, hepatic, and colon cancer cells [14][15][16][17][18]. In a recent study, we showed ATG suppressed metastatic potential and induced autophagic cell death by inhibiting estrogen receptor (ER) expression in MCF-7 human breast cancer cells [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Arctiin and ATG (Figure 2(a)), the main compounds of AL, have been reported to contain a variety of biological activities [36]. Among those compounds, we selected ATG because it has been shown to have beneficial biopharmaceutical properties and activities in the treatment of many diseases [37, 38].…”
Section: Resultsmentioning
confidence: 99%